UM OLHAR ACADÊMICO SOBRE A APLICAÇÃO DE CONFORTO AMBIENTAL NAS DISCIPLINAS DE PROJETO ARQUITETÔNICO - Morsch, Maiara; Kurtz, Sulâni; Nunes, Luana Valéria (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This article presents the reflections of the didactic experience from integration of environmental confort in the teaching of architectural design practice. These Cases Studies starts on the knowledges gained in confort to analyze two projects, an Inn and a Cultural Center, made respectively on the fourth and sixth semester of the course. In the Inn was obligatory use of certain strategies however did not have a mentor specialize in environmental confort, and in the Cultural Center did not have these requirements about strategies, however have a mentor in confort. In short, it was observed the need to exist a teacher in confort area for master the subject more and be able to build a bridge between teaching and practicing of the profession, instigating even more the academic. So that showing the viabilization, disseminate this practice effectively.